Cryptographic protocol to data exchange in hostile machines - de Paulo, Alex Fabianne; Ilmério Reis da Silva; Souza, João Nunes (International Journal of Scientific Research and Management (IJSRM), 2021)
The technology continuous advancement, especially of Internet, has allowed the evolution of the computers usage from a situation that it was used just for simple and isolated tasks to the current global integration level, in which it wants to join the diverse points of generation and use of the information inside and outside of an institution. This has created several possibilities to improve the service quality and information access. On the other hand, new challenges like information heterogeneity and secure appear. This paper presents a new XML-based cryptographic protocol to access and manipulate encrypted data in machines that are susceptible to intruder’s attacks. Following the RSA algorithm, this new protocol defines rules in which the encrypted data are handled independent from the user keys and without access of intruders in the others encryption keys and plain text.